Cycloaddition Reactions of Epoxides and CO2 by the Novel Imidazolium‐Functionalized Metalloporphyrins: Optimization and Analysis using Response Surface Methodology. Issue 19 (28th July 2020) - Li, Zhonglu; Su, Zhenping; Xu, Wenhua; Shi, Qing; Yi, Jiajia; Bai, Caihe; Wang, Ning; Li, Jun
Abstract: The production of cyclic carbonates using CO2 and epoxides has received great attention due to 100 % atom utilization. Herein, novel imidazolium‐containing metalloporphyrins were synthesized as bifunctional catalysts for the cycloaddition reactions of epoxides and CO2 . The reaction conditions were optimized and analyzed with the response surface methodology. Under the optimum condition using Zn‐porphyrin 1 as the catalyst, the turnover number (TON) and turnover number frequency (TOF) for the cycloaddition of CO2 and ECH were 11, 629 and 1, 735, respectively. In addition, analysis of the RSM indicated that the CO2 pressure had only a small impact on the yield. Based on this conclusion, the catalytic activity of 1 was further evaluated under mild conditions. Regardless of whether the CO2 pressure is high or ambient, this Zn‐porphyrin exhibited an excellent performance with a high turnover number frequency. Abstract : Herein, novel imidazolium‐containing metalloporphyrins were synthesized as bifunctional catalysts for the cycloaddition reactions of epoxides and CO2 . The reaction conditions were optimized and analyzed with the response surface methodology. Regardless of whether the pressure of CO2 is high or ambient, the Zn‐porphyrin 1 exhibited an excellent catalytic activity for the cycloaddition reactions of epoxides and CO2 to produce cyclic carbonates.